Adopting Roman Habits – The Baths in the House of Orpheus in Nea Paphos as a ‘Troublesome’ Case Study? - Rekowska, Monika; Michaelides, Demetrios; Christodoulou, Skevi; Kaniszewski, Jakub (Études et Travaux, 2021)
The House of Orpheus at Nea Paphos in Cyprus, a multiphase residential complex excavated a few decades ago, is the subject of an on-going study within the framework of a new project. Recently, the bath suite in the north-eastern part of the house was analysed in detail and this has led to a better understanding of the baths’ layout and technology (such as the water management and heating system), features that confirm the adoption of the western/Italian model, while some of the details remained typical of the Eastern Mediterranean.